Evaluasi Penerapan Seiri, Seiton, Seiso, Seiketsu dan Shitsuke di PT Dynacast Indonesia - Lumbantoruan, Paskadian E; Zetli, Sri (Computer Science and Industrial Engineering, 2020)
Seiketsu and Shitsuke which in Indonesian is concise, neat, clean, care and diligent. PT Dynacast Indonesia's Final Sorting After Plating Department, which consists of 3 production lines. There are still many items or materials that are placed not in accordance with the place, wrong label of the trash. In addition, many tools or materials which are not really needed but are put or placed in them such as trolleys, used cardboard and laying cleaning tools very close to the production table which according to the researchers are things that can be disrupt the production process. The results of the study using the Audit Checklist method found that the level of application. The results of the discussion show that the level for line S1 is categorized as sufficient (53.95%), line S2 is categorized as sufficient (47.81%) and line S3 is categorized sufficiently (42.98%). The proposed improvements obtained are elimination procedures, tagging of goods, location for items in all work areas, storage area labels, location of goods in an easily accessible location, cleaning checklist, picket schedule, socialization of 5S application to employees, work instructions (5S standard poster), visual boards and rewards.